Stable liquid foams from a new polyfluorinated surfactant. Issue 43 (23rd April 2020) - Russo, Maria; Amara, Zacharias; Fenneteau, Johan; Chaumont-Olive, Pauline; Maimouni, Ilham; Tabeling, Patrick; Cossy, Janine
Abstract : The microfluidic production of highly stable foams using newly synthetized polyfluorinated surfactants is reported herein. Abstract : Liquid foams exhibiting long-term stability are a key-challenge in material design. Based on this perspective, new pyridinium polyfluorinated surfactants were synthesized from simple building blocks enabling unusually stable liquid foams. While the batch-generated foams were used for qualitative foaming evaluation, microfluidics allowed a quantitative insight into the aging effects of monodisperse foams.